Reduction of Neuroinflammation as a Common Mechanism of Action of Anorexigenic and Orexigenic Peptide Analogues in the Triple Transgenic Mouse Model of Alzheimer ́s Disease - Mengr, Anna; Šmotková, Zuzana; Pačesová, Andrea; Železná, Blanka; Kuneš, Jaroslav; Maletínská, Lenka (Journal of neuroimmune pharmacology, 2025)
Alzheimer's disease (AD) is the most common form of dementia. Characterized by progressive neurodegeneration, AD typically begins with mild cognitive decline escalating to severe impairment in communication and responsiveness. It primarily affects cerebral regions responsible for cognition, memory, and language processing, significantly impeding the functional independence of patients. With nearly 50 million dementia cases worldwide, a number expected to triple by 2050, the need for effective treatments is more urgent than ever. Recent insights into the association between obesity, type 2 diabetes mellitus, and neurodegenerative disorders have led to the development of promising treatments involving antidiabetic and anti-obesity agents. One such novel promising candidate for addressing AD pathology is a lipidized analogue of anorexigenic peptide called prolactin-releasing peptide (palm11-PrRP31). Interestingly, anorexigenic and orexigenic peptides have opposite effects on food intake regulation, however, both types exhibit neuroprotective properties. Recent studies have also identified ghrelin, an orexigenic peptide, as a potential neuroprotective agent. Hence, we employed both anorexigenic and orexigenic compounds to investigate the common mechanisms underpinning their neuroprotective effects in a triple transgenic mouse model of AD (3xTg-AD mouse model) combining amyloid-beta (Aβ) pathology and Tau pathology, two hallmarks of AD. We treated 3xTg-AD mice for 4 months with two stable lipidized anorexigenic peptide analogues - palm11-PrRP31, and liraglutide, a glucagon-like peptide 1 (GLP-1) analogue - as well as Dpr3-ghrelin, a stable analogue of the orexigenic peptide ghrelin, and using the method of immunohistochemistry and western blot demonstrate the effects of these compounds on the development of AD-like pathology in the brain. Palm11-PrRP31, Dpr3-ghrelin, and liraglutide reduced intraneuronal deposits of Aβ plaque load in the hippocampi and amygdalae of 3xTg-AD mice. Palm11-PrRP31 and Dpr3-ghrelin reduced microgliosis in the hippocampi, amygdalae, and cortices of 3xTg-AD mice. Palm11-PrRP31 and liraglutide reduced astrocytosis in the amygdalae of 3xTg-AD mice. We propose that these peptides are involved in reducing inflammation, a common mechanism underlying their therapeutic effects. This is the first study to demonstrate improvements in AD pathology following the administration of both orexigenic and anorexigenic compounds, highlighting the therapeutic potential of food intake-regulating peptides in neurodegenerative disorders.
Keywords: Animals; myši transgenní; presenilin-1; amyloidový prekurzorový protein beta; ghrelin; Amyloid beta-Peptides; Mice, Transgenic; lidé; amyloidní beta-protein; hormon uvolňující prolaktin; Mice; Neuroinflammatory Diseases; myši; Prolactin-Releasing Hormone; Humans; neurozánětlivé nemoci; liraglutid; Male; modely nemocí na zvířatech; Neuroprotective Agents; Alzheimer Disease; Disease Models, Animal; Ghrelin; Liraglutide; Alzheimerova nemoc; Amyloid beta-Protein Precursor; zvířata; mužské pohlaví; Mice, Inbred C57BL; Presenilin-1; myši inbrední C57BL; neuroprotektivní látky